2005
DOI: 10.5395/jkacd.2005.30.1.038
|View full text |Cite
|
Sign up to set email alerts
|

Relative efficacy of three Ni-Ti file systems used by undergraduates

Abstract: The purpose of this study was to compare and evaluate the shaping ability of the three different Ni-Ti file systems used by undergraduate students.Fifty undergraduate students prepared 150 simulated curved root canals in resin blocks with three Ni-Ti file systems -ProFile � (PF), Manual ProTaper � (MPT), Rotary ProTaper � (RPT). Every student prepared 3 simulated root canals with each system respectively. After root canal preparation, the Ni-Ti files were evaluated for distortion or breakage. Assessments were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2006
2006
2010
2010

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 32 publications
1
7
0
Order By: Relevance
“…Particularly, at 2 ㎜ level the two ProTaper systems showed significantly lesser centering ratios than Group H. The ProFile had the better centering ability than the other groups in most of evaluated levels. This finding is consistent with other studies to evaluate the centering ratio or shaping ability of various NiTi files including ProFile 24,28) . Hong et al 24) recommended, through the comparison of various hybrid instrumentation technique, that if the apical regions are to be enlarged wider than ISO 30, it might be better to use a different system 12) .…”
Section: ⅳ Discussionsupporting
confidence: 82%
“…Particularly, at 2 ㎜ level the two ProTaper systems showed significantly lesser centering ratios than Group H. The ProFile had the better centering ability than the other groups in most of evaluated levels. This finding is consistent with other studies to evaluate the centering ratio or shaping ability of various NiTi files including ProFile 24,28) . Hong et al 24) recommended, through the comparison of various hybrid instrumentation technique, that if the apical regions are to be enlarged wider than ISO 30, it might be better to use a different system 12) .…”
Section: ⅳ Discussionsupporting
confidence: 82%
“…It seemed that enlarged coronal canal by crowndown usage of Mtwo file would facilitate the access to apical canal and this could shorten the time lapse of each step in group MC than that of group MT. In other studies 14,24) to compare ProTaper and other instruments, instrumentation time with ProTaper was shorter than other systems under identical experimental conditions. But in this study, the Mtwo file showed shorter preparation time than ProTaper, regardless of using method of Mtwo file.…”
Section: ⅳ Discussionmentioning
confidence: 99%
“…In ProTaper system, tooth structure can be removed excessively when this instrument is left in the canal too long with its active design 21) . It is therefore of utmost importance to follow the manufacturer' s instructions and not to leave the ProTaper to prepare the root canal for longer than 1 second or not to use the ProTaper too much when reaching the desired working length 14) . This precaution would also be applied in Mtwo instruments of group MT in which showed more aberrations.…”
Section: ⅳ Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…11 Treatment techniques and instruments have been effectively evaluated in randomized controlled studies. [12][13][14][15][16] However, the special prospective cohort study models have been proposed to assess the outcome of endodontic treatment and elucidate the effect of various preoperative factors on the outcome in several studies. [7][8][9][10] A conspicuous aspect of these studies was the identified inception cohort, standardized treatment procedures, and data recording at the start of the study.…”
Section: Introductionmentioning
confidence: 99%